(untitled) (Ágora Journal, 2022)
In line with the evidence of female agency in the public and political spheres in Rome, we intend, in this article, to investigate the performance of different matrons in the North African cities of Oea, Sabrata and Lepcis Magna, urbes associated with the Roman Empire at the middle of the 1st century BC. We defend, here, that such women had a prominent participation in families strategies of social ascension to orders of the elite in Roman society. As evidenced by literary and by some epigraphic inscriptions, the rich matrons acted in the process of ascension her people, either by some diverse matrimonial aliances or by evergetism and relationships with important members of the Roman ruling estate, such as emperors and proconsuls.